COVID-19-related strokes are associated with increased mortality and morbidity: A multicenter comparative study from Bengaluru, South India. Issue 4 (June 2021) - Mathew, Thomas; John, Saji K; Sarma, GRK; Nadig, Raghunandan; Kumar R, Shiva; Murgod, Uday; Mahadevappa, Manjunath; Javali, Mahendra; Acharya, Purushottam Thammaya; Hosurkar, Guruprasad; Krishnan, Pramod; Kamath, Vikram; et al.
Background: COVID-19-related strokes are increasingly being diagnosed across the world. Knowledge about the clinical profile, imaging findings, and outcomes is still evolving. Here we describe the characteristics of a cohort of 62 COVID-19-related stroke patients from 13 hospitals, from Bangalore city, south India. Objective: To describe the clinical profile, neuroimaging findings, interventions, and outcomes in COVID-19-related stroke patients. Methods: This is a multicenter retrospective study of all COVID-19-related stroke patients from 13 hospitals from south India; 1st June 2020–31st August 2020. The demographic, clinical, laboratory, and neuroimaging data were collected along with treatment administered and outcomes. SARS–CoV-2 infection was confirmed in all cases by RT-PCR testing. The data obtained from the case records were entered in SPSS 25 for statistical analysis. Results: During the three-month period, we had 62 COVID-19-related stroke patients, across 13 centers; 60 (97%) had ischemic strokes, while 2 (3%) had hemorrhagic strokes. The mean age of patients was 55.66 ± 13.20 years, with 34 (77.4%) males. Twenty-six percent (16/62) of patients did not have any conventional risk factors for stroke. Diabetes mellitus was seen in 54.8%, hypertension was present in 61.3%, coronary artery disease in 8%, and atrial fibrillation in 4.8%. Baseline National Institutes of Health Stroke Scale score was 12.7 ± 6.44. Stroke severity was moderate (National Institutes of Health Stroke Scale 5–15) in 27 (61.3%) patients, moderate to severe (National Institutes of Health Stroke Scale 16–20) in 13 (20.9%) patients and severe (National Institutes of Health Stroke Scale 21–42) in 11 (17.7%) patients. According to TOAST classification, 48.3% was stroke of undetermined etiology, 36.6% had large artery atherosclerosis, 10% had small vessel occlusion, and 5% had cardioembolic strokes. Three (5%) received intravenous thrombolysis with tenecteplase 0.2 mg/kg and 3 (5%) underwent mechanical thrombectomy, two endovascular and one surgical. Duration of hospital stay was 16.16 ± 6.39 days; 21% (13/62) died in hospital, while 37 (59.7%) had a modified Rankin score of 3–5 at discharge. Hypertension, atrial fibrillation, and higher baseline National Institutes of Health Stroke Scale scores were associated with increased mortality. A comparison to 111 historical controls during the non-COVID period showed a higher proportion of strokes of undetermined etiology, higher mortality, and higher morbidity in COVID-19-related stroke patients. Conclusion: COVID-19-related strokes are increasingly being recognized in developing countries, like India. Stroke of undetermined etiology appears to be the most common TOAST subtype of COVID-19-related strokes. COVID-19-related strokes were more severe in nature and resulted in higher mortality and morbidity. Hypertension, atrial fibrillation, and higher baseline National Institutes of Health Stroke Scale scores were associated with increased mortality.